ANALISIS KEAUSAN PAHAT PADA VARIASI DIAMETER MATA BOR BENCH DRILL IXION BT 25 - Meldi Tumetel; Rudy Poeng; I Nyoman Gede (JURNAL POROS TEKNIK MESIN UNSRAT, 2022)
This research is a test method carried out on the IXION BT 25 bench drill machine which has been developed using a cooling system. After the drill process is carried out on the test object, the drill chisel is measured for tool wear using a digital microscope measuring instrument.From the results of the measurement of drill chisel wear, it is obtained that a drill diameter of 8 mm results a tool wear of 0.3608 microns, a drill diameter of 12 mm brings a tool wear of 0.0540 microns. Whereas, a drill diameter of 17 mm results a tool wear of 0.1030 microns and a drill diameter of 23 mm brings a tool wear of 0.0108 microns. From these results, tool wear that occurs in the drilling process using the coolant developed on the IXION BT 25 bench drill machine will decrease with the larger the drill diameter. From the correlation analysis, it is found th at the relationship between drill diameter and tool wear tends to be very close with a correlation coefficient of 0.78467 and shows that the drill diameter and tool wear have opposite directions.Â Keywords: Chisel Wear, Drill Bit Diameter, Bench Drill Machine IXION